The Influence Of Lifestyle And Financial Literacy On The Behavior Of Housewives In Badas Village, Kediri District In Using Buy Now Pay Later Services - Rodziyah, Fatimatur; Afandi, Tjetjep Yusuf; Surindra, Bayu (International Journal of Economic Research and Financial Accounting, 2024)
This research is motivated by the fact that lifestyle and financial literacy are factors that influence the financial decisions and financial management of housewives. This research focuses on analyzing the influence of lifestyle and financial literacy on the behavior of housewives in Badas Village, Kediri Regency in using buy now pay later services. The method for collecting samples using purposive sampling technique with a total of 97 respondents. Research using quantitative approaches and causality research methods. The results of the study were processed with the SPSS version 23 program, with the conclusion that the lifestyle and financial literacy of housewives of Badas Village, Kediri Regency play an important role in the use of buy now pay later services.  Specifically, this study found that higher lifestyle scores are positively correlated with a higher likelihood of using buy now pay later services. In contrast, higher financial literacy scores are negatively correlated with the use of buy now pay later services.